Investigating the Effectiveness of the Integrated Intervention Model Based on Acceptance, Compassion, and Mindfulness on Psychological Distress and Intolerance of Uncertainty in Nurses with Anxiety in the Emergency Department - Abdolahi, Elnaz; Nasri, Maryam; Shahabizadeh, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the effectiveness of an integrated intervention model based on acceptance, compassion, and mindfulness in reducing psychological distress and intolerance of uncertainty in nurses with anxiety working in emergency departments. Methods and Materials: The study employed a quasi-experimental design with pre-test and post-test assessments and included an experimental and control group. A total of 40 nurses with anxiety working in emergency departments were selected using purposive sampling. Participants were randomly assigned to either the experimental (n=20) or control group (n=20). The experimental group underwent 12 sessions (60 minutes each) of the integrated intervention, while the control group received no intervention. Data were collected using the Kessler Psychological Distress Scale (Kessler et al., 2003) and the Intolerance of Uncertainty Scale (Freeston et al., 1994). The results were analyzed using analysis of covariance (ANCOVA). Findings: The results showed a significant reduction in psychological distress in the experimental group compared to the control group (F(1, 37) = 256.42, p < .001). Similarly, there was a significant reduction in intolerance of uncertainty in the experimental group compared to the control group (F(1, 37) = 63.73, p < .001). These findings indicate that the intervention effectively reduced both psychological distress and intolerance of uncertainty in the experimental group. Conclusion: The integrated intervention model based on acceptance, compassion, and mindfulness was effective in reducing psychological distress and intolerance of uncertainty in nurses with anxiety. This intervention provides a practical approach for addressing emotional difficulties faced by nurses, helping them cope with the stress of their profession, improve their psychological flexibility, and align their actions with their life values. These findings suggest that such interventions can improve the mental well-being of healthcare workers, particularly those in high-stress environments like emergency departments.